Solar energy feasibility for power generation in lower shire districts: A case study of Chikwawa District - Zaunda, Randy (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Electricity availability is an essential part of both economic and non-economic activities in any country. Malawi being one of the developing nations experiences a lot of challenges both in its economic and non-economic activities due to unlimited levels of electric supply in its country. This inadequacy of limited supply has remained a challenge for a longer period of time to the effect that the country Malawi for a longer period of time has an overwhelming record of blackouts and load shedding. Consequently, this has affected in a negative way the economic activities of this nation such as low productivity in the production of goods and services making livelihood a difficult. Similarly, noneconomic activities such social interactions seem to be challenging due to lack of electricity. In this regard an investigation in determining new innovations towards electricity production remained one of the most important aspects in this county of Malawi. Method: This study was conducted in Chikwawa district, Malawi, to assess the feasibility of solar energy production. The methods used include temporal variability, correlation, trend, and spatial analysis to assess solar radiation, sunshine hours, and their distribution in the area. Result: As a result, the study was established with the purpose to assess feasible regions within the country of Malawi to innovate solar energy production to boost high levels of solar energy production. This study was conducted in the lower shire district and to be specific in Chikwawa district. The objectives of the feasibility in Chikwawa district included; assessing solar radiation and sunshine hours towards solar energy production, the spatial distribution of solar radiation and sunshine hours towards solar energy production, the trend of sunshine and solar radiation towards solar production and at the end to map the areas in Chikwawa District where solar energy production could be harnessed. Through the use of temporal variability, correlation analysis, trend analysis, and spatial analysis, the findings of this investigation established that harnessing solar energy is much more possible in areas of the lower shire which is the among others include Chikwawa district of Malawi as most areas currently in this region has less places with solar energy production but with high availability of solar radiation. Conclusion: For the fact that the findings reveal more feasible places to establish solar energy production, this study recommends commitment by government and private sector to greatly establish solar energy production units in this area whilst focusing on identifying other potential areas where solar energy production can be harnessed in Malawi. In this regard, this exposition has achieved its purpose of fostering renewable energy production through innovating and investing in solar energy production. Novelty/Originality of this study: This detailed spatial and temporal analysis study has identified optimal locations for solar energy production, providing a new approach to renewable energy planning in developing countries.